Bolívar's last sentence - Luis Ayala, José (2019)
This article describes the last moments in the life of Simón Bolívar through historical studies and the first-hand testimony of the doctor who assisted the Liberator, Dr. Alejandro Próspero Révérend. It also contrasts and complements the historical facts with Ricardo Palma’s vision of the final moments of the Liberator described in his tradition “La última frase de Bolívar”.